2015
DOI: 10.1002/jssc.201500418
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and accurate liquid chromatography and tandem mass spectrometry method for the simultaneous quantification of ten metabolic reactions catalyzed by hepatic cytochrome P450 enzymes

Abstract: The hepatic cytochrome P450 enzymes play a central role in the biotransformation of endogenous and exogenous substances. A sensitive high-throughput liquid chromatography with tandem mass spectrometry assay was developed and validated for the simultaneous quantification of the products of ten metabolic reactions catalyzed by hepatic cytochrome P450 enzymes. After the substrates were incubated separately, the samples were pooled and analyzed by liquid chromatography with tandem mass spectrometry using an electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Hydroxylation of testosterone by human CYPsr eviewed by Agematu et al,[43] and Niwa et al,[49] and by the more recently reported human,[50][51][52] and bacterial[44,[53][54][55][56] CYPs is shown. Hydroxylation of testosterone by human CYPsr eviewed by Agematu et al,[43] and Niwa et al,[49] and by the more recently reported human,[50][51][52] and bacterial[44,[53][54][55][56] CYPs is shown.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Hydroxylation of testosterone by human CYPsr eviewed by Agematu et al,[43] and Niwa et al,[49] and by the more recently reported human,[50][51][52] and bacterial[44,[53][54][55][56] CYPs is shown. Hydroxylation of testosterone by human CYPsr eviewed by Agematu et al,[43] and Niwa et al,[49] and by the more recently reported human,[50][51][52] and bacterial[44,[53][54][55][56] CYPs is shown.…”
mentioning
confidence: 88%
“…Scheme2.Possiblep ositions of testosterone hydroxylation by different cytochromes P450. Hydroxylation of testosterone by human CYPsr eviewed by Agematu et al,[43] and Niwa et al,[49] and by the more recently reported human,[50][51][52] and bacterial[44,[53][54][55][56] CYPs is shown. The new 1a-hydroxylase activity of CYP260A1 from S. cellulosum So ce56i sa lso included.ChemBioChem 2016, 17,90-101 www.chembiochem.org 2 016 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim…”
mentioning
confidence: 88%
“…Simultaneous determination of acetaminophen, 6‐hydroxychlorzoxazone, 7‐hydroxycoumarin, dextrorphan, 5‐hydroxyomeprazole, 1‐hydroxymidazolam, 6β‐hydroxytestosterone, hydroxylbupropion and 4‐hydroxytolbutamide by liquid chromatography with tandem mass spectrometry (LC–MS/MS) was performed as described previously . Briefly, LC separations were achieved using a Hypersil Gold C 18 (100 mm × 2.1 mm, 3 μm) with a guard column (10 mm × 2.1 mm, 3 μm).…”
Section: Methodsmentioning
confidence: 99%
“…The reaction was initiated by adding NADPH (1 m m ). After incubation at 37 °C for 30 min, the reaction was terminated and analysed as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…Several methods utilizing the benefits of the LC-MS/MS technique have been developed to evaluate enzymatic activities when cocktail mixtures of different CYP substrates were administered [21,22], typically achieving quantitation levels between 10 and 1500 ng mL −1 [21,23]. However, multi-analyte assays do not reach sensitive optimum lower limits of quantification (LLOQ) and for chlorzoxazone the lowest reported quantification value is 0.1 ng mL −1 [24], hampering a full pharmacokinetics monitoring of chlorzoxazone microdoses.…”
Section: Introductionmentioning
confidence: 99%